2023
DOI: 10.1021/acs.energyfuels.3c01533
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Outlook of Metal–Organic Frameworks as High-Performance Electrocatalysts for Hydrogen Evolution Reaction: A Minireview

Morad El Hanafi,
Amal BaQais,
Mohamed Saadi
et al.

Abstract: The increasing demand for renewable energy technologies to safeguard the natural world has led to electrocatalysis’s emergence as a promising hydrogen generation method. Recently, metal–organic frameworks (MOFs) have attracted interest as electrocatalysts due to their unique characteristics, including expansive surface areas, exceptional porosity, and readily modifiable optical and electronic properties. This review comprehensively summarizes MOFs’ recent improvement in heterogeneous catalysis and their compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 158 publications
(233 reference statements)
0
5
0
Order By: Relevance
“…Moreover, MOFs exhibit the capability to serve as templates for the synthesis of metal oxides, owing to their exceptional attributes, including notable porosity, precise structural characteristics, and a high surface area . Metal oxide nanoparticles derived from MOFs display exceptional properties when compared to their conventionally synthesized counterparts . What is particularly interesting is that the morphology and porosity inherent to the MOF precursor are typically retained in the resultant metal oxide nanoparticles .…”
Section: Various Catalysts Used For Hydrogen Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, MOFs exhibit the capability to serve as templates for the synthesis of metal oxides, owing to their exceptional attributes, including notable porosity, precise structural characteristics, and a high surface area . Metal oxide nanoparticles derived from MOFs display exceptional properties when compared to their conventionally synthesized counterparts . What is particularly interesting is that the morphology and porosity inherent to the MOF precursor are typically retained in the resultant metal oxide nanoparticles .…”
Section: Various Catalysts Used For Hydrogen Generationmentioning
confidence: 99%
“…168 Metal oxide nanoparticles derived from MOFs display exceptional properties when compared to their conventionally synthesized counterparts. 34 What is particularly interesting is that the morphology and porosity inherent to the MOF precursor are typically retained in the resultant metal oxide nanoparticles. 169 Because of their adjustable porous structures, MOFs have been employed as platforms for regulating the dimensions of metal nanoparticles (NPs).…”
Section: Mof-based Catalysts Metal−organic Framework (Mof)-based Cata...mentioning
confidence: 99%
See 1 more Smart Citation
“…The current TRL of organic electrocatalysts is only 3, which is because not only the moderate electrocatalytic performance of organic electrocatalysts com-pared with metal-based electrocatalysts and noble-metal benchmarks but also the limitation on scaling up the synthesis. Many current studies have raised some scalable synthesis of organic electrocatalysts, however, their exhibited electrocatalytic activity is usually not competitive, [135] indicating further research is still required for producing cost-effective organic electrocatalysts on a large scale. Therefore, future studies of organic electrocatalysts should focus on further screening cost-efficient organic electrocatalysts through both experimental proofing and theoretical simulating and simultaneously scaling-up the synthesis to pave the way for their future large-scale commercialization in various kinds of energy-converting devices.…”
Section: Roadmap For Obtaining Highly Active Organic Electrocatalystsmentioning
confidence: 99%
“…Due to the severe environmental pollution and running down of fossil fuels, alternative clean energy resources are highly required. Hydrogen energy, an alternative renewable energy source, has gained a great deal of attention due to its high energy output and zero emission. Electrocatalytic water splitting for clean hydrogen production is considered the most efficient path compared to other hydrogen production strategies. In recent years, it has been demonstrated that Pt-group materials (PGMs) have the highest catalytic activity for the electrocatalytic generation of hydrogen. However, the scarcity and expensive materials like Pt hamper their industrially relevant application of hydrogen production. Owing to these reasons, it is highly important to develop a less expensive, easily available, and non-noble metal-based electrocatalytically active catalyst to substitute Pt for efficient HER processes. …”
Section: Introductionmentioning
confidence: 99%